Out in town. Stage 1+, Oxford Reading Tree Phonics - Hunt, Roderick; Brychta, Alex (OXFORD UK, 2012)
The Level 1 Sounds and Letters books introduce children to environmental sounds in a variety of contexts through beautifully illustrated Oxford Reading Tree picture books. There are picture panels on every spread to focus on certain sounds from the scene and include prompts for adults. A perfect resource to teach Phase 1 of Letters and Sounds.